2022
DOI: 10.3389/fmats.2022.833065
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mechanical Properties of 3D Printed Nanocomposites Composed of Functionalized Plant-Derived Biopolymers and Calcium-Deficient Hydroxyapatite Nanoparticles

Abstract: The combination of plant-derived polymer resins and mineral-based nanoparticles into three dimensional (3D) printable, high-performance nanocomposites suggests a means to improve the sustainability profile of rapid prototyping and additive manufacturing. In this work, our previously published nanocomposite biomaterial system of acrylated epoxidized soybean oil (AESO) and polyethylene glycol (PEGDA) diluent composited with calcium-deficient hydroxyapatite (nHA) nanorods was improved by the substitution of AESO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…[139] Adding these metal nanoparticles enables 3D-printed products to have excellent mechanical properties that match the mechanical properties required for bone tissue engineering. Some inorganic non-metallic nanoparticles are also used to improve the mechanical properties of materials, such as ceramic nanoparticles, [140] hydroxyapatite nanoparticles, [141] and silica nanoparticles, [142] which not only have ideal mechanical properties in bone tissue repair, but also can be used as a source of calcium required for bone repair to promote bone tissue repair. The above enhancement of the mechanical properties of 3D printing products is mainly based on the strong mechanical properties of the nanoparticles themselves to enhance other components to improve the mechanical properties of the original material system.…”
Section: Nanomaterials For Enhancing Mechanical Propertiesmentioning
confidence: 99%
“…[139] Adding these metal nanoparticles enables 3D-printed products to have excellent mechanical properties that match the mechanical properties required for bone tissue engineering. Some inorganic non-metallic nanoparticles are also used to improve the mechanical properties of materials, such as ceramic nanoparticles, [140] hydroxyapatite nanoparticles, [141] and silica nanoparticles, [142] which not only have ideal mechanical properties in bone tissue repair, but also can be used as a source of calcium required for bone repair to promote bone tissue repair. The above enhancement of the mechanical properties of 3D printing products is mainly based on the strong mechanical properties of the nanoparticles themselves to enhance other components to improve the mechanical properties of the original material system.…”
Section: Nanomaterials For Enhancing Mechanical Propertiesmentioning
confidence: 99%
“…CSMA-2 is an isosorbide-based polymer derived from sustainable sources such as starch and cellulose. Sustainable plant-derived photopolymers offer environmentally friendly materials to substitute fuel-based commercial photopolymers [ 3 ]. Isosorbide has desirable stiffness for hard tissue engineering due to its ring structure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the good optical transparency of isosorbide is also advantageous for its development as a 3D printing material, especially for lithography methods. Isosorbide can serve as the backbone for polymers with methacrylate or acrylate groups as the functional groups [ 3 ]. Several studies have demonstrated successful 3D printing with various isosorbide-based composites for hard tissue engineering [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although AESO can be UV cured without any other comonomers [15,16], the addition of small amounts of a crosslinking agent, such as polyethylene glycol diacrylate or polycaprolactone diacrylate, has shown to facilitate its photopolymerization and control the final properties of the polymer networks, such as tensile strength and elongation at the break [17]. For DLP or SLA applications, usually (meth)acrylates with functionality up to three are employed, such as hydroxyethyl methacrylate (HEMA) [22], isobornyl methacrylate (IBOMA) [12,23], isobornylacrylate (IBOA) [24], tetrahydrofurfuryl methacrylate (THFMA) [12], 1,6-hexanediol diacrylate (HDDA), [10,25] polyethylene diacrylate (PEGDA) [26][27][28], trimethylolpropane triacrylate (TMPTA) [10,25] or other compounds such as acryloylmorpholine (ACMO) [10]. A summary of these references has been included, although comparisons between them are difficult due to the different experimental conditions and products used, including the origin of the soybean acrylate oil, either commercial or specifically synthesized for the study.…”
Section: Introductionmentioning
confidence: 99%